The Relationship Between Self-Management and Blood Pressure of Hypertension Sufferers in the Kediri I Health Center Region, Tabanan District - Ni Putu Putri Kumalasari; I Ketut Gama; Komang Ayu Henny Achjar; I Wayan Suardana; I Gusti Ketut Gede Ngurah; I Wayan Mustika (Health Dynamics, 2024)
Background: Cases of hypertension in Indonesia show a significant increase. Hypertension continues to lead to complications when people with hypertension have not implemented self-management regularly. Management of hypertension which includes routine medication and healthy lifestyle changes requires good self-management. The purpose of this study was to determine the relationship between self-management and blood pressure of hypertensive patients in the Kediri I Health Center Working Area. Methods: This study uses a quantitative research design (non-experimental) using a cross-sectional approach. The sample amounted to 82 respondents obtained by purposive sampling technique, who met the inclusion criteria, namely hypertensive patients aged 15-59 years. Data collection instruments used the Hypertension Self-Management Behavior Questionnaire (HSMBQ) and blood pressure measurements using a sphygmomanometer. Results: Data analysis using the Spearman rank test showed the results of ρ = 0.000 and the correlation coefficient r = -0.732 which means that there is a significant and strong relationship (0.60 - 0.79) between the two variables. The majority of respondents showed poor self-management behavior 56.1%. Conclusion: It is hoped that it can be used as information for the relevant health centers, that the importance of implementing self-management to prevent an increase in blood pressure in hypertensive patients.